The Next Society Sociologia del mutamento e dei processi digitali - Bianco, Adele (Computational Social Science - Open Access, 2019)
Contemporary society is undergoing a set of changes and technological innovations. This is the topic of this book. The theoretical starting point of this book is that the complex transition we are witnessing seems to be alike to the rise of the industrial society in the 1800. The today transformations affect the social relationships, shape the social organization, create imbalances and difficulties in adaptation to the new world, meet cultural resistance, require new rules. The book is structured as follows. The first chapter is devoted to the classical theory of social change. The second one deals with the current global transformation trends. The third and fourth chapters focus on the digital processes and innovation technologies as factor of change. The aim is also reconstructing their origins and evolution. The last chapter is devoted to the impact of the digitalization process on the labor market and the organization of work.